2021
DOI: 10.1016/j.jchf.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geographic Region on the COMMANDER-HF Trial

Abstract: OBJECTIVES This study sought to compare patient characteristics, outcomes, and treatment effects among regions in the COMMANDER-HF trial.BACKGROUND Globalization of cardiovascular trials increases generalizability. However, regional differences may also introduce heterogeneity in results.METHODS Incidence rates and interactions with treatment were recorded in pre-specified regions: Eastern Europe,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In HF patients, stroke risk inversely correlates with LV function even in the absence of atrial fibrillation; however, annual stroke risks are lower in contemporary trials than Fig. 4 Calculated event rates for stroke and ISTH-major bleedings in patients with cardiovascular disease and heart failure in sinus rhythm in the Western European subgroup of the COMMANDER-HF trial comparing the factor Xa-inhibitor rivaroxaban at a dose of 2.5 mg twice daily to placebo; ER event rate of both treatments per region in COMMANDER-HF [43], E Plac calculated event rate on placebo, E Riva calculated event rate on rivaroxaban, ISTH-major bleeding major bleeding as defined according to the International society on Thrombosis and Haemostasis [29], RR relative risk on treatment per region as reported for COMMANDER-HF [43] initially predicted. Routine anticoagulation with VKA did not provide a clinical benefit owing to the increased rate of major bleedings and lower than expected stroke rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In HF patients, stroke risk inversely correlates with LV function even in the absence of atrial fibrillation; however, annual stroke risks are lower in contemporary trials than Fig. 4 Calculated event rates for stroke and ISTH-major bleedings in patients with cardiovascular disease and heart failure in sinus rhythm in the Western European subgroup of the COMMANDER-HF trial comparing the factor Xa-inhibitor rivaroxaban at a dose of 2.5 mg twice daily to placebo; ER event rate of both treatments per region in COMMANDER-HF [43], E Plac calculated event rate on placebo, E Riva calculated event rate on rivaroxaban, ISTH-major bleeding major bleeding as defined according to the International society on Thrombosis and Haemostasis [29], RR relative risk on treatment per region as reported for COMMANDER-HF [43] initially predicted. Routine anticoagulation with VKA did not provide a clinical benefit owing to the increased rate of major bleedings and lower than expected stroke rates.…”
Section: Discussionmentioning
confidence: 99%
“…During the 1990s, large heart failure trials such as Survival and Ventricular Enlargement (SAVE) and Studies of Left Ventricular Dysfunction (SOLVD) indicated an increased risk of thromboembolism with decreasing LV-EF postulating an inverse relation of 18% relative increase in stroke per 5% absolute reduction in LV-EF [1][2][3]. In a nationwide Danish cohort study including almost 43.000 patients, of whom only 22% had atrial fibrillation, HF patients had a high ischemic stroke risk, the CHA 2 DS 2 -VASc score modestly predicted the risk, and patients with HF in the absence of atrial fibrillation and CHA 2 DS 2 -VASc scores ≥ 4 had a high absolute risk of ischemic stroke. HF patients without atrial fibrillation and high risk scores had a similar rate of thromboembolism as patients with atrial fibrillation [4].…”
Section: Increased Stroke Risk In Patients With Chronic Heart Failure and Sinus Rhythmmentioning
confidence: 99%
See 3 more Smart Citations